2009
DOI: 10.1542/peds.2007-3723
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia and Language Delay in Premature Infants

Abstract: Objective To evaluate if language delay at three years in premature infants is associated with prior exposure to hyperbilirubinemia during the first two weeks after birth. Patients and Methods We performed retrospective case-control study of infants admitted to the Neonatal Intensive Care Unit between January and October 2003. Inclusion criteria included a birth weight ≤ 1500 grams and follow-up to age three years. Exclusion criteria included genetic disorders and hearing loss or recurrent ear infections. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
0
21
2
Order By: Relevance
“…Moreover, no term Taiwanese infants were classified as having cognitive or motor delay, and only few infants had language delay based on the Bayley-III standard. Meanwhile, preterm Taiwanese infants' cognitive and motor performance approached the Bayley-III norms, and their rates of developmental delay were lower than the previously established prevalence estimates (cognitive delay 0-1% vs. 4-30%, language delay 2-9% vs. 8-26%, and motor delay 0-1% vs. 4-11%) (Amin, Prinzing, & Myers, 2009;Jackson, Needelman, Roberts, Willet, & McMorris, 2012;Kaaresen et al, 2008;Maguire et al, 2009aMaguire et al, , 2009bMossabeb, Wade, Finnegan, Sivieri, & Abbasi, 2012;Mukhopadhyay, Malhi, Mahajan, & Narang, 2010;Peters et al, 2009). The finding concerning the underestimation of the rate of developmental delay by the Bayley-III has also been documented in recent studies of term and preterm infants in Western countries (Acton et al, 2011;Anderson et al, 2010;Esteban et al, 2010;Makrides et al, 2010;Moore et al, 2012;Reuner et al, 2013;Robertson et al, 2010;Spittle et al, 2010;Vohr et al, 2012).…”
Section: Discussioncontrasting
confidence: 54%
“…Moreover, no term Taiwanese infants were classified as having cognitive or motor delay, and only few infants had language delay based on the Bayley-III standard. Meanwhile, preterm Taiwanese infants' cognitive and motor performance approached the Bayley-III norms, and their rates of developmental delay were lower than the previously established prevalence estimates (cognitive delay 0-1% vs. 4-30%, language delay 2-9% vs. 8-26%, and motor delay 0-1% vs. 4-11%) (Amin, Prinzing, & Myers, 2009;Jackson, Needelman, Roberts, Willet, & McMorris, 2012;Kaaresen et al, 2008;Maguire et al, 2009aMaguire et al, , 2009bMossabeb, Wade, Finnegan, Sivieri, & Abbasi, 2012;Mukhopadhyay, Malhi, Mahajan, & Narang, 2010;Peters et al, 2009). The finding concerning the underestimation of the rate of developmental delay by the Bayley-III has also been documented in recent studies of term and preterm infants in Western countries (Acton et al, 2011;Anderson et al, 2010;Esteban et al, 2010;Makrides et al, 2010;Moore et al, 2012;Reuner et al, 2013;Robertson et al, 2010;Spittle et al, 2010;Vohr et al, 2012).…”
Section: Discussioncontrasting
confidence: 54%
“…For example, even relatively slight elevations in perinatal bilirubin levels can generate brain abnormalities, particularly within the basal ganglia [213]. BINDS, or bilirubin-induced neurotoxic disorders, are often associated with the development of cognitive deficits, including problems with attention that reflect disturbance within basal ganglia gating mechanisms [214,215]. Based upon the neuroanatomic position and function of the basal ganglia, disturbances in the gating of sensory perceptions might be predicted as well [216].…”
Section: Discussionmentioning
confidence: 99%
“…Premature infants are at higher risk of bilirubin-induced neurotoxicity compared to term infants consistent with the findings of increased prevalence of ASD among premature infants compared to term infants (Amin 2004; Burd et al 1999; Eaton et al 2001; Larsson et al 2005; Maimburg and Vaeth 2006). Both autism and bilirubin-induced neurotoxicity may also manifest clinically with abnormal auditory evoked responses and impaired communication further suggesting biological plausibility (Amin 2004; Amin et al 2009; Funato et al 1996; Perlstein 1960; Russo et al 2008; Rosenhall et al 2003; Whitehouse and Bishop 2008). Several investigators have demonstrated prolongation of absolute and interpeak latencies of auditory brainstem evoked response in autistic children (Rosenhall et al 2003; Thivierge et al 1990; Wong and Wong 1991).…”
Section: Introductionmentioning
confidence: 99%